Standard methods of chemical analysis : a manual of analytical methods and general reference for the analytical chemist and for the advanced student : the elements - Scott, Wilfred W. (Van Nostrand)
Contenido: Elementos. Pruebas cualitativas de sustancias. Tablas y datos útiles.